BSND and ATP6V1G3. Issue 24 (June 2015) - Shinmura, Kazuya; Igarashi, Hisaki; Kato, Hisami; Koda, Kenji; Ogawa, Hiroshi; Takahashi, Seishiro; Otsuki, Yoshiro; Yoneda, Tatsuaki; Kawanishi, Yuichi; Funai, Kazuhito; Takayama, Tatsuya; Ozono, Seiichiro; et al.
<x xml:space="preserve">Abstract</x> Abstract Differentiating between chromophobe renal cell carcinoma (RCC) and other RCC subtypes can be problematic using routine light microscopy. This study aimed to identify novel immunohistochemical markers useful for a differential diagnosis between chromophobe RCC and other RCC subtypes. We selected 3 genes (including BSND and ATP6V1G3) that showed specific transcriptional expression in chromophobe RCC using expression data (n = 783) from The Cancer Genome Atlas (TCGA) database. A subsequent immunohistochemical examination of 186 RCCs obtained in our patient series resulted in a strong diffuse positivity of BSND and ATP6V1G3 proteins (both of which are involved in the regulation of membrane transport) in all the chromophobe RCC specimens (23/23 cases, 100%) but not in the clear cell RCC specimens (0/153 cases, 0%) or the papillary RCC specimens (0/10 cases, 0%). BSND and ATP6V1G3 protein expressions were also detected in renal oncocytoma (13/14 cases, 92.9%) and in the distal nephron, including the collecting duct, in the normal kidney. A computational analysis of TCGA data suggested that DNA methylation was involved in the differential expression pattern of both genes among RCC subtypes. Finally, an immunohistochemical analysis showed lung carcinomas were negative (0/85 cases, 0%) for the expression of both proteins. These results suggest that BSND and ATP6V1G3 are excellent novel immunohistochemical markers for differentiating between chromophobe RCC and other subtypes of RCC, including clear cell and papillary RCCs.